Unua aliro al la uzo de interjekcioj en Esperanto - Fortes, Fabio (Investigationes Linguisticae, 2021)
Interjections are a class of words found across all natural languages. Their use relates to the expression of mental states or speech acts within the discursive context. Although they are relatively common in natural languages, they represent a class of words that are poorly integrated into the grammar, and therefore, are theoretically less predictable as linguistic elements for planned languages ​​such as Esperanto. In this article, I propose to analyze the use of some interjections in Esperanto. The aim is to understand how competent speakers of this language employ interjections. For this, in the first part I review the literature on the linguistic aspects of interjections, in comparison with the Esperanto grammatical tradition; then I analyze the data related to the use of these words by competent speakers, which I obtained through the application of a survey specially designed for this purpose, which is also described in this article.